Changing Expression Profiles of Messenger RNA, MicroRNA, Long Non-coding RNA, and Circular RNA Reveal the Key Regulators and Interaction Networks of Competing Endogenous RNA in Pulmonary Fibrosis - Liu, Xue; Liu, Huaman; Jia, Xinhua; He, Rong; Zhang, Xinyue; Zhang, Wei (Frontiers in Genetics, 2020)
Abstract Pulmonary fibrosis is a kind of interstitial lung disease with architectural remodeling of tissues and excessive matrix deposition. Apart from mRNA, microRNA, long non- lncRNA and circRNA could also play important roles in the regulatory processes of occurrence and progression of pulmonary fibrosis. In the present study, the pulmonary fibrosis model were administered with bleomycin. Whole transcriptome sequencing analysis was applied to investigate the expression profiles of mRNAs, lncRNAs, circRNAs and miRNAs. After comparing bleomycin-induced pulmonary fibrosis model lung samples and controls, 286 lncRNAs, 192 mRNAs, 605 circRNAs, and 32 miRNAs were found to be differentially expressed. GO and KEGG analyses were performed to investigate the potential functions of these DE mRNAs and ncRNAs. The terms related to inflammatory response and TNF signaling pathway were enriched implying potential roles in regulatory process. In addition, two co-expression networks were also constructed to understand the internal regulating relationships of these mRNAs and ncRNAs. Our study provides a systematic perspective on the potential functions of these DE mRNAs and ncRNAs during PF process, and could help pave the way for effective therapeutics for this devastating and complex disease.